Antimicrobial assay and chromatographic analysis of Lablab (Benthic Mat) extracts. - Cerbo, Rossa Lyn
The Lablab (Benthic mat) sample in this study was predominantly consisted of diatoms, specifically, pleurosigma and the blue green algae, oscillatoria., The antimicrobial study of Lablab showed it to be potential probiotic. The dichloromethane fraction showed the highest antimicrobial activity at 1000 ug/ml against Citrobacter fecundii, Vibrio harveyi, Staphylococcus aureus, and Bacillus subtilis with microbial indices of 1.10, 1.47, 0.63 and 0.93 respectively. The crude methanolic extract was most effective against Aeromonas hydrophila since it showed antimicrobial activity at 10 ug/ml, 100 ug/ml and 1000 ug/ml with microbial indices of 0.10, 0.23 and 0.37, respectively. The fractions generally showed zones of inhibition at 1000 ug/ml. Using the thin layer chromatography, some bioactive compounds were found to be possible present in the fractions obtained from Lablab: Cardiac glycosides, phenolic compounds, saponins, terpenes and flavonoids. The dichloromethane fraction has the most number of components while the ethyl acetate fraction has the least number of components. The DCM fraction was further subjected to two-dimesional thin layer chromatography. Eight spots were located with 5:3 ethyl acetate: dichloromethane and six spots formed with 2:1:1 ethyl acetate: n-hexane: dichloromethane solvent systems. Cardiac glocosides and terpenes were found to be possibly present in the Crude methanolic, h-Hexane, Dichloromethane, Ethyl acetate and Aqueous Extracts when subjected to thin layer chromatography spotted in one plate using 5:2:3 n-Hexane: Dichloromethane: Methanol as the solvent system.